Isolation and Identification of the Thermophilic Amylase-Producing Bacteria from Soil of North of Iran - NAJAFI YASOURI, FAZEL; GHAEMI, NASSER; TANZADEH, JINA (Asian Journal of Chemistry, 2010)
Soil samples were screened from amylase- producing bacteria on starch agar medium (Nutrient Agar containing 1 % soluble starch). Amylase-producing bacteria was identified by clear zones of starch hydrolysis around colonies by flooded with lugol solution. Starch containing areas are coloured dark blue,while areas around the colonies hydrolysis starch were clear,showing the effect of extracellular amylase that had broken the bonds in the starch. 31 Thermostable amylase producing bacteria were isolated from different soil samples (Compost, Hot spring and Manures) collected from various parts of North of Iran. These bacteria were examined for various morphological and biochemical characteristics according of Bergey's manual of determination bacteriology. The best starch degrader were Bacillus species.